The Portrayal of Masculinity Traits in Female Character in Prey Film - Refaldi, Tomas Aditya (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This research focuses on the construction of masculinity in the main female character and the challenges of patriarchy in the Comanche tribe's social condition in the Prey film (2022). Character theory by Pettrie and Boggs (2012) is used to analyze the main female character. Theory of masculinity BSRI 1974 By Dr. Sandra Lipzits Bem is used as a theory in research to analyze masculinity traits in this film. Therefore, the descriptive qualitative method is used as the research method. The results of this study showed that the social condition in the Comanche tribe is a powerful and prolonged patriarchal life. Where the patriarchal life is very limits the rights of Comanche women, this background makes the main female character have masculine characteristics. In changing the patriarchy condition in her tribe, there are three stages that the main female character goes through to achieve this goal. These stages are the challenge of traditional habits by becoming a female hunter, then proving the abilities possessed by the main female character, and the last, the use of an intelligent and analytical hunting method that is different from the usual hunting method. The masculine character continues to exist until the position of main female character is recognized by the tribe, and she becomes the first female hunter in the tribe. In the end, this recognition signifies a change in social conditions and the existing system, with the appointment of women as hunters and tribal leaders. In conclusion, the masculinity traits in female characters arise because of the patriarchal system in the tribe, which encourages the desire to change the existing system by becoming the first female hunter. This indicates the changing and replacement of the patriarchal system in the Comanche tribe in this film.